(untitled) - Guttentag, Marcia (Beverly Hills, 1983)
The basic premise of this provocative book is a startling one - that sex ratios among people on the marriage market have profound consequences for a wide variety of attitudes, values, and behaviors, from sexual mores and behavior to shifts in economic power...the authors share with the reader a wealth of fascinating data and information...a book which is...fascinating, scholarly, provocative and exceedingly well-written.
Keywords: Sex customs,Sex ratio,Tập quán tình dục,Tỷ lệ giới tính; History,History,Social aspects,Lịch sử,Các khía cạnh xã hội,Lịch sử